2019
DOI: 10.1007/978-3-030-19685-1_13
|View full text |Cite
|
Sign up to set email alerts
|

What Start-Up Firms Are More Likely to Obtain Public Funding Support? A Systematic Analysis of the Funding Program Promoted by the Abruzzo Region in Italy

Abstract: material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Rostamkalaei and Freel (2017) surveyed small and medium-sized businesses in the UK and found that seeking financial advice before starting to apply for a loan reduced business risk and resulted in successful loan applications. Corsi et al (2019) examined the data of Italian entrepreneurs and found that manager's age is an important factor in receiving public support.…”
Section: Finance Of Start-up Companiesmentioning
confidence: 99%
“…Rostamkalaei and Freel (2017) surveyed small and medium-sized businesses in the UK and found that seeking financial advice before starting to apply for a loan reduced business risk and resulted in successful loan applications. Corsi et al (2019) examined the data of Italian entrepreneurs and found that manager's age is an important factor in receiving public support.…”
Section: Finance Of Start-up Companiesmentioning
confidence: 99%